(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of this study is to get practical evidence from the Egyptian business environment The Impact of Audit Committees Effectiveness and External Audit Quality on Timeliness of annual Financial Report. Design and methodology: The study based on the content analysis technique to examine the annual reports of a sample of (30) companies listed on the Egyptian Stock Exchange (EGX100) during the period (2016-2019) with a total of (120) respondents. To test the research hypotheses, the results of the study indicate that there is a negative significant impact of audit committees on timeliness of annual financial report. Moreover, while there is a negative impact on the quality of the external audit on the timing of issuing the annual financial report. There is a negative significant impact of audit committees and external audit quality on timeliness of annual financial report. Based on the previous results, the study recommends the necessity of directing attention and developing the awareness of the Managements of Egyptian joint stock companies to take all appropriate procedures, which guaranty avoidance, or limiting the delay in issuing the financial report. By doing these we can achieve fairness and transparency and protect the investor from the risks that he might be exposed to as a result of not publishing the financial reports on time. Practical evidence: The results of the study may be of interest to investors and companies when they determine the factors affecting the timing of issuance of financial reports for business establishments in the Egyptian environment. The results may also provide information that may be useful to the auditing authorities and the financial auditing authority on the motives of business establishments for delaying the issuance of annual financial reports.